Voci della Grande Guerra. An Annotated Corpus of Italian Texts on World War I - Alessandro Lenci; Claudio Marazzini; Nicola Labanca; Simonetta Montemagni (IJCoL)
Voci della Grande Guerra (Voices of the Great War) is a scientific and cultural initiative with the aim of preserving and promoting the memory of Italy in World War I through the creation of a corpus of digital texts selected by historians and linguists in order to be representative of the different ways to experience and describe the Italian war by its protagonists. With the help of advanced techniques of computational linguistics, semantic web and information visualization, the digitized historical materials will be explored with an online interface to enable easy but effective and innovative search modalities. The project will allow experts as well as non-experts to become acquainted with “linguistic polyphony” of Italy during World War I.